2015
DOI: 10.3892/ol.2015.3810
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced pulmonary injury accelerated pulmonary metastasis in a mouse model of breast cancer

Abstract: Abstract. The aim of the present study was to investigate the acceleration of pulmonary metastasis due to pulmonary injury caused by radiation treatment in a mouse model of breast cancer, in addition to determining the associated mechanism. The passive metastatic breast cancer model was used in radiation-treated BALB/c mice. In total, 24 mice were randomly separated into two groups, with 12 mice per group, and the groups were treated with or without pulmonary radiation. The survival time and variation of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Signaling between SDF-1α and CXCR4 contributes to tumor growth, angiogenesis, invasion and metastases in numerous malignancies [ 21 23 ]. In addition, irradiation-enhanced invasiveness of non-small lung cancer and breast cancer has been attributed to the SDF-1α/CXCR4 interaction [ 14 , 24 ]. Moreover, the relationship between MPM and the SDF-1α/CXCR4 chemotactic axis has been reported in previous reports [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signaling between SDF-1α and CXCR4 contributes to tumor growth, angiogenesis, invasion and metastases in numerous malignancies [ 21 23 ]. In addition, irradiation-enhanced invasiveness of non-small lung cancer and breast cancer has been attributed to the SDF-1α/CXCR4 interaction [ 14 , 24 ]. Moreover, the relationship between MPM and the SDF-1α/CXCR4 chemotactic axis has been reported in previous reports [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…111 In a study using radiation-treatment mouse models of breast cancer, Gong et al found that pulmonary injury from radiation-treatment induced CXCL12-CXCR4 overexpression, which resulted in increased number of metastatic nodules in the lungs. 112 Recently, the expression of CXCR4 was reported to be higher in TNBC, which has a propensity for lung metastasis. 113 Although how the CXCL12-CXCR4 axis induces lung metastasis remains unclear, some studies suggest that this may be due to increased macrophages and micro vessel density.…”
Section: 107mentioning
confidence: 99%
“…[30][31][32][33][34][35] Repeated μCT scanning using our high-resolution 4D protocol for 5 weeks and even up to 12 consecutive weeks did not induce any lung damage in healthy mice. 36 Because the dose rate and dose delivered during our μCT study are both at least an order of magnitude smaller than the dose and rate applied in radiotherapy research, [26][27][28][37][38][39][40] it is unlikely that metastases would be affected. This is supported by the lack of differences in Lewis lung carcinoma tumor volume found 21 days after irradiation with a therapeutic dose of 12 Gy compared with unirradiated tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%